High‐fat diet‐induced obesity augments the deleterious effects of estrogen deficiency on bone: Evidence from ovariectomized mice. Issue 12 (10th October 2022) - Ali, Dalia; Figeac, Florence; Caci, Atenisa; Ditzel, Nicholas; Schmal, Clarissa; Kerckhofs, Greet; Havelund, Jesper; Færgeman, Nils; Rauch, Alexander; Tencerova, Michaela; Kassem, Moustapha
Abstract: Several epidemiological studies have suggested that obesity complicated with insulin resistance and type 2 diabetes exerts deleterious effects on the skeleton. While obesity coexists with estrogen deficiency in postmenopausal women, their combined effects on the skeleton are poorly studied. Thus, we investigated the impact of high‐fat diet (HFD) on bone and metabolism of ovariectomized (OVX) female mice (C57BL/6J). OVX or sham operated mice were fed either HFD (60%fat) or normal diet (10%fat) for 12 weeks. HFD‐OVX group exhibited pronounced increase in body weight ( 86% in HFD and 122% in HFD‐OVX, p < 0.0005) and impaired glucose tolerance. Bone microCT‐scanning revealed a pronounced decrease in trabecular bone volume/total volume (BV/TV) (−15.6 ± 0.48% in HFD and −37.5 ± 0.235% in HFD‐OVX, p < 0.005) and expansion of bone marrow adipose tissue (BMAT; +60.7 ± 9.9% in HFD vs. +79.5 ± 5.86% in HFD‐OVX, p < 0.005). Mechanistically, HFD‐OVX treatment led to upregulation of genes markers of senescence, bone resorption, adipogenesis, inflammation, downregulation of gene markers of bone formation and bone development. Similarly, HFD‐OVX treatment resulted in significant changes in bone tissue levels of purine/pyrimidine and Glutamate metabolisms, known to play a regulatory role in bone metabolism. Obesity and estrogen deficiency exert combined deleterious effects on bone resulting in accelerated cellular senescence, expansion of BMAT and impaired bone formation leading to decreased bone mass. Our results suggest that obesity may increase bone fragility in postmenopausal women. Abstract : Obesity in female mice, when combined with estrogen deficiency, has a detrimental impact on bone quality, caused by expansion of bone marrow adiposity, upregulation of pro‐inflammatory markers, upregulation of senescence‐associated phenotype markers and accumulation of senescent cells. This also resulted in downregulation of anabolic bone formation pathways, osteoporotic bone phenotype, and increased fracture risk.